1D Core‐shell MnO@S, N co‐Doped Carbon for High Performance Lithium Ion Battery Anodes. Issue 41 (5th November 2019) - Liu, Xiao‐Jun; Zhong, Ming; Wu, Hongtao; Yue, Bin
Abstract: Manganese monoxide (MnO) is a promising anode material for lithium ion batteries, but it often shows poor electrochemical performance due to some inevitable drawbacks including intrinsic low electrical conductivity, poor stability, and severe polarization. In this work, a 1D core‐shell MnO@S, N co‐doped carbon material (MnO@SNC) was obtained by pyrolysis of MnO2 @PPy precursor at 600 °C in N2 atmosphere. When evaluated as an anode for lithium ion batteries, the unique structure and composition advantages endow the as‐formed material with excellent lithium storage performance in terms of high specific capacity (955.5 mAh g −1 at a current density of 500 mA g −1 ), long‐term cycling stability (up to 500 cycles), and superior rate capability (458.7 mAh g −1 at a current density of 2 A g −1 ). The outstanding electrochemical performance could be attributed to the unique 1D core‐shell structure, abundant graphited carbon and MnO nanorods. Abstract : A unique core‐shell MnO@S, N co‐doped carbon nanorod material was successfully prepared through a novel one‐step carbonization of MnO2 @PPy precursor. Owing to many superiorities including the inherent core‐shell structure, existed MnO active component, and carbon coating, the as‐formed material delivers excellent lithium storage performance in terms of high capacity up to 955.5 mAh g −1, long cycling lifespan for 500 cycles, and outstanding rate capability.